Secularism in Turkey as a Nationalist Search for Vernacular Islam - Umut Azak (Revue des Mondes Musulmans et de la Méditerranée)
This article analyzes one of the reforms of the Kemalist state which imposed the recitation of the Turkish translation of the call to prayer and banned its original Arabic version between 1932 and 1950. This reform reflected the nationalist urge to create an Islam unaffected by the Arabic language and Arab cultural traditions. The ban on the call to prayer in Arabic was part of a wider nationalist program which aimed to Turkify all cultural fields including religion and to promote a local vernacular Islam. This intervention was in line with official secularism, because the latter did not mean the total exclusion of Islam from the public sphere, but its control and even its endorsement as long as it remained loyal to the modernist state.